The Geography of Medicare - Cutler, David M; Sheiner, Louise (American Economic Review, 1999)
There is a great deal of geographic variation in Medicare spending. For example, while the average Medicare cost per beneficiary was around $5200 in 1996, Medicare spending, adjusted for diffences in regional prices and demographic composition, was about $8000 per person in Miami, but only $3500 in Minneapolis. In this paper, we explore the source of this variation. We find that a substantial amount can be explained by differences across areas in the health of the elderly population. This finding suggests that some of the geographic variation in Medicare spending is efficient. But even accounting for differences in the health of the population, significant variation remains. We have been able to explain some of the remaining variation. The strongest factors are supply variables: for-profit hospitals and specialist physicians both increase Medicare spending. If these factors are exogenous, public policy may want to consider the supply of medical services more than it currently does. We do not find that expensive places spend a disproportionate amount on those near death.